2022
DOI: 10.1002/jmri.28488
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Estimating Vessels Encapsulating Tumor Clusters in Hepatocellular Carcinoma From Preoperative Gadoxetate Disodium‐Enhanced MRI

Abstract: Background Vessels encapsulating tumor clusters (VETC) pattern is a novel microvascular pattern associated with poor outcomes of hepatocellular carcinoma (HCC). Preoperative estimation of VETC has potential to improve treatment decisions. Purpose To develop and validate a nomogram based on gadoxetate disodium‐enhanced MRI for estimating VETC in HCC and to evaluate whether the estimations are associated with recurrence after hepatic resection. Study Type Retrospective. Population A total of 320 patients with HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…Their models were established after deep learning of the radiomic features of intratumoral and peritumoral tissues and are as follows: on non-rim dh-APHE, the tumor signal intensity (SI)/liver SI ratio is ≥1.135 in AP, and the tumor SI/liver SI ratio in HPB is ≤0.585, conferring high accuracy for predicting VETC-HCC. Furthermore, heterogeneous enhancement is an important factor in assessing VETC patterns, with positive VETC patterns being more frequently found when heterogeneous enhancement includes irregular ring-like structures or septum-like structures [51]. The imaging features of two HCC subtypes are shown in Table 1.…”
Section: Mrimentioning
confidence: 99%
“…Their models were established after deep learning of the radiomic features of intratumoral and peritumoral tissues and are as follows: on non-rim dh-APHE, the tumor signal intensity (SI)/liver SI ratio is ≥1.135 in AP, and the tumor SI/liver SI ratio in HPB is ≤0.585, conferring high accuracy for predicting VETC-HCC. Furthermore, heterogeneous enhancement is an important factor in assessing VETC patterns, with positive VETC patterns being more frequently found when heterogeneous enhancement includes irregular ring-like structures or septum-like structures [51]. The imaging features of two HCC subtypes are shown in Table 1.…”
Section: Mrimentioning
confidence: 99%
“…However, evaluating VETC patterns preoperatively remains challenging because VETC can only be diagnosed by surgical specimens. Some studies have tried to use preoperative imaging to noninvasive evaluate VETC 8–12 . Computed tomography (CT) or MRI features, such as types of enhancement pattern, intratumoral necrosis, tumor size, and non‐rim diffuse and heterogeneous arterial phase hyperenhancement (non‐rim dh‐APHE), have been reported to be associated with VETC 8–11 .…”
mentioning
confidence: 99%
“…[8][9][10][11][12] Computed tomography (CT) or MRI features, such as types of enhancement pattern, intratumoral necrosis, tumor size, and non-rim diffuse and heterogeneous arterial phase hyperenhancement (non-rim dh-APHE), have been reported to be associated with VETC. [8][9][10][11] Yu et al predicted the preoperative VETC and prognosis of HCC patients based on radiomics features of the hepatobiliary phase (HBP) of gadolinium-ethoxybenzyldiethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced MRI. 12 However, the criteria for preoperative imaging diagnosis of VETC have not been widely accepted, and more robust evidence is needed.…”
mentioning
confidence: 99%
“…6,7 In this issue of Journal of Magnetic Resonance Imaging, the authors reported MR imaging features that can predict the presence of VETC pattern, and tumor size, presence of heterogeneous enhancement, and necrosis were significantly associated with the VETC pattern. 8 In addition, the authors developed a nomogram based on MR imaging features to predict the presence of VETC pattern with a good discrimination performance. This study had several strengths.…”
mentioning
confidence: 99%
“…The nomogram based on MR imaging features including tumor size, heterogeneous enhancement, and presence of necrosis was an accurate model to predict the VETC pattern and predictive of high recurrence after surgery. 8 Given that, MR imaging features that can predict the presence of VETC would be helpful for HCC management by accurately estimating the risk of tumor recurrence, ultimately leading to the selection of optimal treatment plans.…”
mentioning
confidence: 99%